EFFECTS OF PARTIAL REPLACEMENT OF RATTAN POWDER BY COMMERCIAL FILLERS ON THE PROPERTIES OF NATURAL RUBBER COMPOSITES - Muniandy, Komethi; Ismail, Hanafi; Othman, Nadras (Bioresources, 2012)
The effects of partial replacement of rattan powder (RP) by carbon black (CB), mica, and calcium carbonate (CaCO3) on the curing characteristics, tensile properties, rubber-filler interaction, and morphological studies of natural rubber (NR) composites were investigated. Rattan powder with an average particle size of less than 180 µm was used in this study. NR/RP/CB, NR/RP/mica, and NR/RP/CaCO3 composites with five different RP/commercial fillers loadings (i.e. 30/0, 20/10, 15/15, 10/20, 0/30 phr) were prepared using a laboratory size two-roll mill. Results showed that the maximum torque (MH) of the NR/RP/CB, NR/RP/mica, and NR/RP/CaCO3 composites increased with increasing the commercial filler-loading ratio. The scorch time (ts2) and cure time (t90) of NR/RP/CB composites decreased as the ratio of CB loading was increased, whereas, ts2 and t90 of NR/RP/mica and NR/RP/CaCO3 composites increased as mica and CaCO3 loading ratio were raised, respectively. The tensile strength, elongation at break (Eb), stress at 100% elongation (M100), and stress at 300% elongation (M300) of all the composites increased as the commercial filler-loading ratio increased. This is due to the presence of the commercial filler, which brought a better rubber-filler interaction, as confirmed by the rubber-filler interaction and scanning electron microscopy (SEM) studies.